Heat Thermodynamics and Statistical Physics - Lal, Brij : N. Subrahmanyam : P.S. Hemne (New Delhi : S. Chand, 1968)
Chemistry and Physics
Keywords: Heat; Thermodynamics; Thermometry -- Expansion -- Calorimetry